From Drama to Change: The Role of Female-Led Egyptian TV Dramas in Tackling Women’s Issues and Inspiring Youth - Bader, Myrna (AUC Knowledge Fountain, 2025)
The media is widely recognized as a powerful tool for driving social change, shaping public opinion, and influencing societal discourse. In Egypt, it has played a critical role in addressing women’s issues, including discrimination and societal challenges, by raising awareness and either reinforcing or challenging societal issues. This paper examines the impact of female-led Egyptian TV dramas in addressing women’s issues, specifically taboos, stereotypes, and personal status laws. The paper aims to examine their potential to raise awareness, challenge cultural norms, and inspire youth-driven social change. To achieve its objectives, three female-led Egyptian TV dramas addressing specific women’s societal issues were analyzed for their impact on youth (ages 20–35) through an online survey with 291 responses (N = 291). While the sample size provides useful insights, its size is slightly smaller than ideal for accurately representing the larger population. This may slightly limit how well the findings apply to all Egyptian youth aged 20-35. Using Social Cognitive Theory and Cultivation Theory as theoretical frameworks, the findings revealed that greater exposure to these dramas led to increased awareness among youth and influenced their opinions on the issues addressed in each series. The findings revealed that for (H1), (H2), and (H3), analyzed separately for each series, the significance value (p-value) was < 0.001, leading to the rejection of the null hypothesis and confirming that all three hypotheses were statistically significant and supported across all three TV dramas. Additionally, the survey also found that youths' willingness to participate in initiatives aimed at empowering women was relatively high, with mean scores ranging from M = 4.46 to M = 4.53 (SD = 0.61–0.67), regardless of their level of exposure. This suggests that youths’ willingness to act may be influenced by factors beyond media exposure, such as pre-existing values, social environments, or education. However, this study does not aim to explain a cause-and-effect relationship; rather, it argues that a correlation exists between the tested variables. A relationship is evident between exposure, awareness, and willingness to participate, but no causal link is established. This suggests that while media exposure plays an important role in raising awareness and influencing opinion, other factors like personal beliefs, cultural background, and social influences also contribute to shaping people’s willingness to take part in social initiatives.